Simple and effective solution for diaphragm pacing by that uses the transvenous femoral approach in a patient treated with cardiac resynchronization-defibrillator therapy: The wrapping method - Alper, Ahmet Taha (J Arrhythm, 2017)
The use of cardiac resynchronization therapy (CRT) has become widespread in patients with heart failure who meet the criteria for implantation. Coronary sinus lead positioning is important to provide the intended biventricular stimulation. Diaphragm pacing is a lead-related complication which occurs secondary to phrenic nerve stimulation. We present the case of a 58-year-old male patient who had diaphragm pacing after CRT with defibrillator implantation. The complication was resolved by using the transvenous femoral approach with the wrapping method.